Quality and readability of web-based information on dental caries in Arabic: an infodemiological study - Khalid Aboalshamat (BMC, 2023)
Abstract Background Web-based information on dental caries in Arabic remains poorly understood. This study aimed to assess the quality and readability of web-based information about dental caries in Arabic. Methods The first 100 websites in Arabic about dental caries were retrieved from Google and Bing using common terms. The websites were classified and evaluated for quality based on the Journal of the American Medical Association (JAMA) benchmark criteria, the DISCERN tool, and the presence of the Health on the Net Foundation Code of Conduct (HONcode). Readability was assessed using online readability indexes. Results A total of 102 Arabic websites were included. The JAMA benchmark score was low (m = 0.36, SD = 0.56), with 67.7% failing to meet any of the JAMA criteria. The DISCERN total score mean was 37.68 (SD = 7.99), with a majority (67.65%) of moderate quality. None of the websites had the HONcode. Readability was generally good, with 52.94% of websites having a Flesch-Kincaid Grade Level (FKGL) < 7, 91.18% having a Simple Measure of Gobbledygook (SMOG) < 7, and 85.29% having a Flesch reading ease (FRE) score ≥ 80. There was a positive correlation between JAMA and DISCERN scores (p < 0.001). DISCERN scores were positively correlated with the number of words (p < 0.001) and sentences (p = 0.004) on the websites. However, JAMA or DISCERN scores were not correlated with FKGL, SMOG, or FRE scores (p > 0.05). Conclusions The quality of Arabic dental caries websites was found to be low, despite their readability. Efforts are needed to introduce more reliable sources for discussing dental caries and treatment options on sites aimed at Arabic populations.